Antileishmanial pharmacomodulation in 8-nitroquinolin-2(1H)-one series. Issue 10 (15th May 2015) - Kieffer, Charline; Cohen, Anita; Verhaeghe, Pierre; Paloque, Lucie; Hutter, Sébastien; Castera-Ducros, Caroline; Laget, Michèle; Rault, Sylvain; Valentin, Alexis; Rathelot, Pascal; Azas, Nadine; Vanelle, Patrice
Graphical abstract: Abstract: An antileishmanial pharmacomodulation at position 4 of 8-nitroquinolin-2(1 H )-one was conducted by using the Sonogashira and Suzuki–Miyaura coupling reactions. A series of 25 derivatives was tested in vitro on the promastigote stage of Leishmania donovani along with an in vitro cytotoxicity evaluation on the human HepG2 cell line. Only the derivatives bearing a phenyl moiety at position 4 of the quinoline ring displayed interesting biologic profile, when the phenyl moiety was substituted at the para position by a Br or Cl atom, or by a CF3 group. Among them, molecules17 and19 were the most selective and were then tested in vitro on the intracellular amastigote stage of both L. donovani and Leishmania infantum, in parallel with complementary in vitro cytotoxicity assays on the macrophage cell lines THP-1 and J774A.1. Molecule19 showed no activity on the amastigote stages of the parasites and some cytotoxicity on the J774A.1 cell line while molecule17, less cytotoxic than19, showed anti-amastigote activity in L. infantum, being 3 times less active than miltefosine but more active and selective than pentamidine. Nevertheless, hit-molecule17 did not appear as selective as the parent compound.